ATRIBUT MORAL TENTANG KESABARAN ALLAH DINYATAKAN SECARA UTUH KEPADA AYUB - Sostenis Nggebu (STT Saint Paul Bandung, 2021)
The purpose of this article is to highlight God's patience with Job. That even though God was misunderstood by both Job and his friends, God still showed his unwavering image-as a long-patient and loving figure. That’s way I’m interested to explore God's patience to respond to Job's complaints towards God. At first, God seems withdrawn Himself from his life. After studied Jobs’ text, I learn that God's patience towards Job from his story shouldn’t be missed, we need to studying more specifically. From Job, we as God’s followers able to truly understand God's patience with Job then this precious truth becomes a strength to hold on to when we are facing hardship in this life. When Job places the sovereign of God between himself and the trials so he was protected from outside attacks through the arguments of his three egocentric companions who tend to accuse and judgemental over Job. From Job's narrative of his suffering, it appears that although his life is so threatening, God never breaks in His promise exactly the same as what he believes about God's faithfulness. God is righteous, patient, and full of affection to Job in every season he faces. God is Yahweh in charge of restoring Jobs' life, and that He is also God sovereign over His people all the time.